Distribution Characteristics of Anammox Bacteria in Ancient Canal (Guyun River) Riparian Sediment of Zhenjiang, China. Issue 3 (16th March 2019) - Zhou, Xiaohong; Li, Yimin; Wen, Chunzi; Liu, Dan
Abstract: Riparian sediment is an important active interface zone for nitrogen-biogeochemical cycles. However, the distribution characteristics of anammox bacteria are not adequately described in the riparian sediment of urban rivers. Therefore, the distribution characteristics of anammox bacteria of Guyun river riparian sediment, which is the representative urban river, were investigated in this study. Research results showed that anammox bacterial abundance showed a significant spatial variation at the study area. Abundance values ranged from 2.00 × 10 5 to 1.92 × 10 7 copies·g −1  dry sediment. And the average value was 6.64×10 6 copies·g −1 dry sediment in six collected samples. Abundance of anammox bacteria was significantly related to TN, NH4 + -N, and pH. Slight spatial variations of richness and diversity in Guyun river riparian sediment were obtained and physicochemical parameters of sediment samples did not significantly influence the biodiversity index of anammox bacteria. Phylogenetic analysis indicated that all amplified sequences fell within the known anammox bacterial group, i.e., Brocadia, Anammoxoglobus/Jettenia, and Kuenenia, with proportions of 33.91%, 24.35%, and 41.74%, respectively. The relative abundance of anammox bacteria showed distinctive spatial heterogeneity in six different sample sites. This finding indicated a distinct spatial variation of anammox bacterial in Guyun river riparian sediment.